The Role of Adequate Nutrition on Early Stages of Child Development. New Aspects of Goat Milk-Based Infant Formulas Implementation - Sergey G. Gribakin ("Paediatrician" Publishers LLC, 2022)
The early stages of child development are characterized by various processes of maturation such as brain growth and development. The digestive and immune systems are developing as well at the same time. The intestinal microbiota plays significant role in the development of all organs and systems. Various disorders of microbial colonization of digestive system can negatively affect food programming processes. Nutrition type (breastfeeding or artificial) also has its own noticeable effect on early development. Breastfeeding is the "gold standard" in children's nutrition. Modern approaches on creation of adapted formulas based on goat's milk allow to develop its optimal composition (protein fraction for easy digestion, -palmitate, oligosaccharides, and natural nucleotides) that has positive effect on the child's development.